PENGARUH PEMBERIAN AIR REBUSAN DAUN SALAM (Syzgium polyanthum) TERHADAP KADAR HDL DAN LDL KOLESTEROL SERUM MENCIT (Mus musculus L.) JANTAN HIPERLIPIDEMIA - Kartikaningrum, Vidya (Widya Warta, 2018)
Hiperlipidemia refers to heightening levels of lipid in the blood. Hyperlipidemia relates closely to the change of HDL levels and the heightening of LDL levels. One of the ingredient to decrease the cholesterol levels in the blood is Syzgiumpolyanthum. The research was aimed to find out the effects of Syzgiumpolyanthum’s boiled water therapy on hiperlidemia, viewed from the levels of HDL and LDL.The research was using 12 male mice ( Mus muschulus L). Mice were divided in four groups. Ovulation inductions were applied for 7 daysto make hyperlipidemia mice model. Therapies were done for 7 days using Syzgiumpolyanthum’s boiled water 2,7ml  and 5,4 ml dosage.One Way AnalisisOf Variance (ANOVA) were employed in the research with Duncan’s advance test for LDL and HDL levels. The results showed that Syzgiumpolyanthum’s boiled water had significant effect to decrease  the levels of LDL and to increase the levels of HDL in hiperlipidemia of  mice (Musmusculus L).